Unleashing the power of pixels: Digital gaming as an unconventional catalyst for spontaneous Language learning in an EFL environment - Djoko Sutrisno; Noor Azlinda Zainal Abidin (Teaching English as a Foreign Language Journal, 2023)
In the past two decades, the world has witnessed an exponential rise in the use of digital games, thanks to the widespread availability of Personal Computers (PCs) and mobile devices. These games have not only provided entertainment but have also demonstrated both positive and negative effects on players. While numerous studies have explored the impact of digital games on attention span, concentration, and addiction, little attention has been given to their influence on incidental Foreign Language acquisition. To bridge this research gap, the researcher embarked on a three-month longitudinal observational study during the post Covid-19 pandemic in 2022. The goal was to explore how digital games, which young learners played for leisure at home, affected their unintentional acquisition of English as foreign language. Participants in the study ranged from 8 to 14 years old, and three popular games, namely Free Fire, Minecraft, and Among Us, were included in the experiment. The results of our study shed light on the significant impact of digital gaming on participants' vocabulary development, highlighting gaming as a valuable asset for foreign language acquisition. Moreover, the players displayed a remarkable ability to retain the newly acquired vocabulary. However, we did identify two drawbacks. Firstly, the prolonged screen time associated with gaming raised concerns. Secondly, we observed that the vocabulary acquired was often specific to certain areas within a particular game, limiting its transferability to broader language contexts. This study serves as a catalyst for further research, encouraging an exploration of the benefits and drawbacks of employing digital games for targeted aspects of foreign language acquisition, such as cognitive skill development and enhanced comprehension. By delving deeper into these areas, researchers can better understand how digital games can be optimized to foster effective language learning experiences. Ultimately, this knowledge will contribute to the design of educational games that leverage the potential of digital technologies to facilitate language acquisition and promote a holistic learning experience for young learners